Los procesos de Régimen Especial y su incidencia en el presupuesto de la Empresa Eléctrica Riobamba S.A., año 2020. - Paguay Zula, Karla Jhoanna (2023)
In the present research work, the processes will analyze the Special Regime to determine their incidence in Empress Electric Riobamba S.A.'s budget in the year 2020. Because the institution makes acquisitions of goods and services through the different public procurement processes, therefore, a field and documentary investigation will be carried out through the application of a survey of the population corresponding to the public procurement area of the institution since it identified if the processes comply with their different phases correctly and the analysis of its assigned budget. In the same way, when carrying out the study of the different characteristics and numerical data of the investigation, it took into account that the research project was done according to the interpretation of the appropriate information according to the theoretical framework. The research project is comprised of chapters. First, the referential framework is developed where the introduction, problematization, and investigation objectives are specified. The second chapter presents the theoretical framework where all the information is presented based on the topic. Of study, in the third chapter consists of the research methodology, which describes the research type, the population, and the instruments raised, among others. The fourth chapter comprises the results and the discussion, and the fifth chapter consists of the conclusions and recommendations of the work.